Immunomodulatory effects of pharmaceutical opioids and antipyretic analgesics: Mechanisms and relevance to infection. Issue 7 (1st March 2022) - Abdel Shaheed, Christina; Beardsley, Justin; Day, Richard O.; McLachlan, Andrew J.
Abstract : Understanding how pharmaceutical opioids and antipyretic analgesics interact with the immune system potentially has major clinical implications for management of patients with infectious diseases and surgical and critical care patients. An electronic search was carried out on MEDLINE, EMBASE, PsycINFO, CENTRAL and the Cochrane library to identify reports describing the immunomodulatory effects of opioid analgesics and antipyretic analgesics, and their effects in infectious diseases. In adaptive immunity, nonsteroidal anti‐inflammatory drugs have divergent effects: augmenting cell‐mediated immunity but inhibiting humoral immunity. Nonsteroidal anti‐inflammatory drugs have demonstrated a beneficial role in Mycobacterium tuberculosis infection and histoplasmosis in animals, and may be plausible adjuvants to antimicrobial agents in these diseases. There is a need to evaluate these findings rigorously in human clinical trials. There is preliminary evidence demonstrating antiviral effects of indomethacin in SARS CoV‐2 in vitro; however, uncertainty regarding its clinical benefit in humans needs to be resolved in large clinical trials. Certain opioid analgesics are associated with immunosuppressive effects, with a developing understanding that fentanyl, morphine, methadone and buprenorphine suppress innate immunity, whilst having diverse effects on adaptive immunity. Morphine suppresses key cells of the innate immunity and is associated with greater risk of infection in the postsurgical setting. Efforts are needed to achieve adequate analgesia whilst avoiding suppression of the innate immunity in the immediate postoperative period caused by certain opioids, particularly in cancer surgery.